Effects of Fungicide and Adjuvant Sprays on Nesting Behavior in Two Managed Solitary Bees, Osmia lignaria and Megachile rotundata - Artz, Derek R. (Public Library of Science, 2015)

(untitled) (PLoS One)
There is a growing body of empirical evidence showing that wild and managed bees are negatively impacted by various pesticides that are applied in agroecosystems around the world. The lethal and sublethal effects of two widely used fungicides and one adjuvant were assessed in cage studies in California on blue orchard bees, Osmia lignaria, and in cage studies in Utah on alfalfa leafcutting bees, Megachile rotundata. The fungicides tested were Rovral 4F (iprodione) and Pristine (mixture of pyraclostrobin + boscalid), and the adjuvant tested was N-90, a non-ionic wetting agent (90% polyethoxylated nonylphenol) added to certain tank mixtures of fungicides to improve the distribution and contact of sprays to plants. In separate trials, we erected screened cages and released 20 paint-marked females plus 30–50 males per cage to document the behavior of nesting bees under treated and control conditions. For all females in each cage, we recorded pollen-collecting trip times, nest substrate-collecting trip times (i.e., mud for O. lignaria and cut leaf pieces for M. rotundata), cell production rate, and the number of attempts each female made to enter her own or to enter other nest entrances upon returning from a foraging trip. No lethal effects of treatments were observed on adults, nor were there effects on time spent foraging for pollen and nest substrates and on cell production rate. However, Rovral 4F, Pristine, and N-90 disrupted the nest recognition abilities of O. lignaria females. Pristine, N-90, and Pristine + N-90 disrupted nest recognition ability of M. rotundata females. Electroantennogram responses of antennae of O. lignaria females maintained in the laboratory did not differ significantly between the fungicide-exposed and control bees. Our results provide the first empirical evidence that two commonly used fungicides and a non-ionic adjuvant can disrupt nest recognition in two managed solitary bee species.